Analysis of the Level of Motivation to Learn Science Considered from 4 Main Indicators: SE, IE, CDL, and CCI - Sholihah, Mar'atus; Rohmani, Rohmani; Suprapto, Irawan (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2024)
Learning motivation is one of the important factors that influence the success of the learning process, especially in Natural Science (IPA) subjects that require an in-depth understanding of concepts. This study aims to analyze the level of motivation to learn science in 5th-grade students at MIN 3 Lampung Utara. Learning motivation is measured based on four main indicators, namely Self-Efficacy (SE), Interest and Enjoyment (IE), Connection to Daily Life (CDL), and Cross-Cultural Interactions (CCI), which are adapted from Ginzburg & Barak's research (2023). Data were collected by distributing questionnaires directly to students, and the data were analyzed using the Rasch model. The results showed that the motivation to learn science at MIN 3 Lampung Utara was in the high category, with an average percentage of motivation of 71.67%. The results of the analysis using the Rasch model show person reliability of 0.78 and item reliability of 0.85, which indicates that the instrument used has good consistency in measuring science learning motivation. Furthermore, an in-depth analysis of the four indicators showed that overall student motivation was high. However, the Connection to Daily Life (CDL) indicator, which reflects students' ability to connect science material with daily life, showed the lowest score compared to other indicators. This finding has important implications for educators and curriculum developers to improve the relevance of science learning to students' daily lives. Therefore, further research is needed to explore the factors that influence the low connection between science materials and students' daily life contexts.